2008
DOI: 10.5713/ajas.2008.70292
|View full text |Cite
|
Sign up to set email alerts
|

An Intravenous Replenishment of Salivary Components and Dry Forage Intake in Freely Drinking Large-type Goats

Abstract: Large-type goats eating dry forage secreted large volumes of saliva which resulted in the loss of NaHCO 3 from the blood and decreased plasma volume (hypovolemia). This research investigated whether or not the loss of NaHCO 3 from the blood and hypovolemia brought about by dry forage feeding actually depresses feed intake in large-type goats under free drinking conditions. The present experiment consisted of three treatments (NI, ASI, MI). All treatments in this experiment were carried out under free drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Blair-West and Brook (1969) reported that changes in hematocrit and plasma total protein concentration reflected the changes in circulating plasma volume. Sunagawa et al (2008) reported that in large-type goats fed dry forage, hematocrit and plasma total protein concentration rapidly increased with dry forage feeding while plasma osmolality increased very slowly. Consistent with the results reported by Sunagawa et al (2008), in both the NFC control and the SFC treatment of the present experiment, after the commencement of dry forage feeding hematocrit and plasma total protein concentration increased to levels higher than pre-feeding levels.…”
Section: Thirst Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Blair-West and Brook (1969) reported that changes in hematocrit and plasma total protein concentration reflected the changes in circulating plasma volume. Sunagawa et al (2008) reported that in large-type goats fed dry forage, hematocrit and plasma total protein concentration rapidly increased with dry forage feeding while plasma osmolality increased very slowly. Consistent with the results reported by Sunagawa et al (2008), in both the NFC control and the SFC treatment of the present experiment, after the commencement of dry forage feeding hematocrit and plasma total protein concentration increased to levels higher than pre-feeding levels.…”
Section: Thirst Levelmentioning
confidence: 99%
“…Sunagawa et al (2008) reported that in large-type goats fed dry forage, hematocrit and plasma total protein concentration rapidly increased with dry forage feeding while plasma osmolality increased very slowly. Consistent with the results reported by Sunagawa et al (2008), in both the NFC control and the SFC treatment of the present experiment, after the commencement of dry forage feeding hematocrit and plasma total protein concentration increased to levels higher than pre-feeding levels. Hematocrit and plasma total protein concentrations in the SFC treatment were greater than those in the NFC control.…”
Section: Thirst Levelmentioning
confidence: 99%
“…Values are means± standard error of 6 large-type goats. a,b Means with different superscripts differ (p<0.05) from the non-infusion control (NI) ( Sunagawa et al, 2008 ).…”
Section: Figurementioning
confidence: 99%
“…In countries such as Japan where ruminants are raised in barns, most farmers feed their livestock a diet of dry forage twice a day. In NFC when goats were fed on dry forage for 2 h twice daily, irrespective of whether drinking water was supplied ( Nagamine et al, 2003 ; Sunagawa et al, 2003 ; 2008 ) or withheld ( Sunagawa et al, 2002 ; 2007 ) during feeding, eating rates rapidly decreased in the first 30 or 40 min of feeding and were subsequently reduced to very low rates for the reminder of the 2 h feeding period. The low eating rates mean that dry forage intake significantly decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation